IMPLEMENTASI PERPRES NO. 49 TAHUN 2021 DALAM FASILITASI PERIZINAN INVESTASI PADA SEKTOR PARIWISATA DIKAITKAN DENGAN KOMITMEN INDONESIA PADA IA-CEPA (INDONESIA AUSTRALIA - COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT) - Anisha Dwi Utami Sunandar, (2023)
In recent years, there has been an increase in diplomatic ties between Indonesia and Australia, especially in the economic field, with the development of free trade and investment. This analysis aims to help Indonesia capitalize on its good relations in tourism to increase its benefits as Australia's 13th largest trading partner. The use of the IA-CEPA will widen, including buying and selling of goods, services and investments. This connection will also encourage other fields such as health, education, telecommunications, tourism, transportation, and expansion of workforce capacity. This is also a strategic partnership that will improve the food industry and advanced industries and develop human resources. At the same time, Indonesia can also avoid the possibility of failing in the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) due to modifications to the rules that bind Indonesia and Australia's commitments. By analyzing these activities, it was found that Indonesia made many regulatory changes to the guidelines for the Indonesia-Australia Comprehensive Economic Partnership Agreement (IA-CEPA) which resulted in the perception of a violation of commitments by partner countries. This research method uses a qualitative approach, namely by using secondary data. Collection techniques with library research (library research).